The Technology Processing of "4 Care" Home Care Application Based on Artificial Intelligence - Fifiana Teresia Lilianira; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Dadan Ramdhani (Journal of Multidisciplinary Academic, 2020)
As a company that focuses on digital start-up, the information technologies systems are become a very important factor for the continuity of Four Care's business. In this study, we will explain the process flow that occurs from the front end to the backend of technology over Four Care applications. It will emphasize backend technology process as the core of this business.